Music as A Therapeutic Medium at Kyai Ageng Majapahit Semarang Orphanage Foundation (Jurnal Seni Musik, 2023)
Music plays several significant roles in life, one of which is as a medium for healing and therapy. The objective of this study was to identify and describe the utilization of music as a therapeutic medium at the Kyai Ageng Majapahit Orphanage Foundation in Semarang. The use of music as a therapeutic medium at the Kyai Ageng Majapahit Orphanage Foundation in Semarang is evident in terms of the musical form and the application process. This study employed qualitative descriptive method. The data collection techniques included observation, interviews, and documentation. The data analysis used interactive model, and data validity was ensured through triangulation of data, sources, and time. The findings reveal that the form of music employed in music therapy activities at the Kyai Ageng Majapahit Orphanage Foundation in Semarang involves the use of tambourine musical instrument. The process of music therapy itself takes place in the school building's hall owned by the Kyai Ageng Majapahit Orphanage Foundation in Semarang, and employs specific methods and considers various crucial aspects throughout the music therapy process. The objective of music therapy activities utilizing tambourine is not only entertainment but also serves as a relaxation therapy medium for foster children, particularly those with anxiety disorders.